ANALISIS HUKUM PERLINDUNGAN PENCIPTA ATAS KOMERSIALISASI LAGU YANG DILAKUKAN OLEH TELEVISI INDOSIAR - Fadyah Suci Wulandari; Simona Bustani (Fakultas Hukum Universitas Trisakti, 2021)
Protection of Intellectual Property Rights on copyright which includes economic rights and moral rights of the creator and/or copyright holder is needed, with the violation of the announcement and/or reproduction of copyrighted works that are not done with permission or license agreement. The formulation of this problem is how the arrangement of the legal protection of songwriters Bukan Pengemis Cinta based on the Copyright Act and how the role of LMK and LMKN in copyright protection. The research method used is normative, this research is descriptive, the type of data used is primary and secondary data, qualitative data analysis, and methods to draw conclusions using deductive logic. The results of this research, discussion and conclusion are the legal protection arrangements of creators and / or copyright holders have been regulated in UUHC in 2014 and PP No. 56 of 2021 this confirms the mandate of UUHC 2014 regarding royalty payments, LMK and LMKN play an important role for that, the establishment of this Institution is a way of solving problems experienced by creators and/or copyright holders who often experience obstacles in maintaining their economic rights to the commercialization of their copyrighted works.